Knockdown of TANK-Binding Kinase 1 Enhances the Sensitivity of Hepatocellular Carcinoma Cells to Molecular-Targeted Drugs - Du, Fengxia; Sun, Huiwei; Sun, Fang; Yang, Shiwei; Tan, Haidong; Li, Xiaojuan; Chai, Yantao; Jiang, Qiyu; Han, Dongdong (Frontiers in Pharmacology, 2022)
The protein kinase, TANK-binding kinase 1 (TBK1), not only regulates various biological processes but also functions as an important regulator of human oncogenesis. However, the detailed function and molecular mechanisms of TBK1 in hepatocellular carcinoma (HCC), especially the resistance of HCC cells to molecular-targeted drugs, are almost unknown. In the present work, the role of TBK1 in regulating the sensitivity of HCC cells to molecular-targeted drugs was measured by multiple assays. The high expression of TBK1 was identified in HCC clinical specimens compared with paired non-tumor tissues. The high level of TBK1 in advanced HCC was associated with a poor prognosis in patients with advanced HCC who received the molecular-targeted drug, sorafenib, compared to patients with advanced HCC patients and a low level of TBK1. Overexpression of TBK1 in HCC cells induced their resistance to molecular-targeted drugs, whereas knockdown of TBK1 enhanced the cells’ sensitivity to molecular-targeted dugs. Regarding the mechanism, although overexpression of TBK1 enhanced expression levels of drug-resistance and pro-survival-/anti-apoptosis-related factors, knockdown of TBK1 repressed the expression of these factors in HCC cells. Therefore, TBK1 is a promising therapeutic target for HCC treatment and knockdown of TBK1 enhanced sensitivity of HCC cells to molecular-targeted drugs.